Visual Branding of Sikapak Timur Village Pariaman as Media Promotion Based on Visual Complexity Effect on Social Media - Firosha, Ardian; Gusman, Taufik; Sumema; Rotama, Hendra (International Journal of Advanced Science Computing and Engineering, 2023)
Visual Complexity Effect is a term used in psychology to describe how people react to complex visual information. Typically, the more complicated or complex the visual information, the more difficult it is for people to process and understand it. The effects of visual complexity can also affect reaction times, cognitive abilities, and decision making. In everyday life, data visualization and complex graphs can be a challenge for many people, especially if they are not used to that type of information. Therefore, graphic designers and application developers try to minimize visual complexity so that it can be understood and used easily by users.